CTIM-11. PHASE I/II STUDY TO EVALUATE THE SAFETY AND CLINICAL EFFICACY OF ATEZOLIZUMAB (ATEZO) IN COMBINATION WITH TEMOZOLOMIDE (TMZ) AND RADIATION IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA (GBM). (9th November 2020) - Weathers, Shiao-Pei; Kamiya-Matsuoka, Carlos; Harrison, Rebecca; Liu, Diane; Sanqui, Edmund; Dervin, Shannon; Yun, Cindy; Loghin, Monica; Penas-Prado, Marta; Majd, Nazanin; Yung, W K Alfred; O'Brien, Barbara; et al.
Abstract: BACKGROUND: Immunotherapy strategies such as PD-1/PD-L1 inhibition may work synergistically with radiation, which is known to increase antigen presentation and promote a pro-inflammatory tumor microenvironment. This trial evaluated the safety and clinical efficacy of concurrent atezo (anti-PD-L1) with radiation therapy and TMZ followed by adjuvant atezo and TMZ in patients with newly diagnosed GBM, unselected for MGMT status. METHODS: Eligibility criteria included patients age > 18 yrs who had undergone only surgery. The primary endpoint was safety in Phase I (n = 10) and OS in Phase II (n = 50). Secondary endpoints included progression free survival (PFS), overall response rate (ORR), and duration of response. All 60 patients were evaluated for efficacy. Correlative endpoints include profiling tumor immune cell populations, peripheral blood for circulating chemokines/cytokines, and stool for gut microbiome. RESULTS: 60 patients were enrolled. With a median follow-up time of 17.1 months (data cutoff = 15 April 2020), 37 patients have progressed, of which 30 patients have died. Median OS was 19 months (95% CI: 14.9, not reached). Median PFS was 10.6 months (95% CI: 8.2–16.7). Median OS in MGMT methylated patients (n = 18) was 29.9 months (95% CI: 11.4, not reached) and 16.3 months (95% CI: 13.9, not reached) in MGMT unmethylated patients (n = 33). Treatment-related adverse events with maximum CTCAE grade > 3 occurred in 33 patients; the most common were LFT elevation (n = 5) and lymphopenia (n = 23). To date, 20 of the enrolled 60 patients underwent re-resection post atezo treatment. The matched paired tumor analysis of pre and post treatment tissue will provide valuable insights into mechanisms of anti-PD-L1 therapy resistance. Tumor immunocorrelative studies are pending. CONCLUSIONS: Concurrent use of atezo with radiation and TMZ was tolerable and demonstrated efficacy in line with published trials for newly diagnosed GBM.